2020
DOI: 10.1186/s12891-020-03738-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pediatric lateral condylar humerus fractures with closed reduction and percutaneous pinning

Abstract: Background Lateral condylar humerus fractures (LCHFs) are the second most common pediatric distal humerus fractures. Open reduction and internal fixation is recommended for fractures displaced by more than 2 mm. Few studies described using closed reduction and percutaneous pinning (CRPP) for treating fractures with greater displacements. This study aims to explore the feasibility of CRPP in treating displaced LCHFs. Methods All patients underwent attempted CRPP first. Once a satisfying reduction was obtained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 20 publications
3
32
1
Order By: Relevance
“…For such cases, it is recommended that CRPP should be attempted first, and if this fails, ORIF should be performed [ 1 , 2 , 9 ]. However, there is no consensus about the optimal treatment for LCHFs displaced by > 4 mm: most clinicians advocate for the use of ORIF, and only a few recommend CRPP [ 1 – 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For such cases, it is recommended that CRPP should be attempted first, and if this fails, ORIF should be performed [ 1 , 2 , 9 ]. However, there is no consensus about the optimal treatment for LCHFs displaced by > 4 mm: most clinicians advocate for the use of ORIF, and only a few recommend CRPP [ 1 – 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients achieved fracture union. The final follow-up found no dysfunction or major complications [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors stated that it is common practice to perform an arthrogram after closed reduction and percutaneous pinning (CRPP) of minimally displaced lateral condyle fractures (LCFs) but in contrary to the former, we could only identify five other articles in the literature which documented the use of an arthrogram after CRPP [2][3][4][5][6]. Two of the former authors [2,3] stated that the arthrogram did not change the treatment decision, two [4,5] did not provide this information and Xie et al [6] reported a conversion of CRPP to open reduction and K-wire fixation (ORIF) in 10 of 46 patients. Kang et al [7] converted nine of 39 CRPPs to ORIF after arthroscopic assessment.…”
mentioning
confidence: 99%